2004
DOI: 10.1074/jbc.m402759200
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of Sulfite Neurotoxicity

Abstract: Exposure of Neuro-2a and PC12 cells to micromolar concentrations of sulfite caused an increase in reactive oxygen species and a decrease in ATP. Likewise, the biosynthesis of ATP in intact rat brain mitochondria from the oxidation of glutamate was inhibited by micromolar sulfite. Glutamate-driven respiration increased the mitochondrial membrane potential (MMP), and this was abolished by sulfite but the MMP generated by oxidation of malate and succinate was not affected. The increased rate of production of NADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 50 publications
(53 reference statements)
4
53
0
Order By: Relevance
“…SO, which is localized in the mitochondrial intermembrane space oxidizes sulfi te to sulfate, thus no accumulation of sulfi te in the cytosol or extracellular compartments is seen under wild-type conditions [ 67 ]. In MoCD and SOD, sulfi te accumulates fi rst in mitochondria where it has been shown to increase reactive oxygen species [ 149 ]. Sulfi te also decreases ATP synthesis in mitochondria when respiring on glutamate (which is the case in the brain), while using other respiratory substrates such as malate, α-ketoglutarate, and succinate did not show any sulfi te vulnerability [ 149 ].…”
Section: Molecular Basis Of Neurodegenerationmentioning
confidence: 97%
“…SO, which is localized in the mitochondrial intermembrane space oxidizes sulfi te to sulfate, thus no accumulation of sulfi te in the cytosol or extracellular compartments is seen under wild-type conditions [ 67 ]. In MoCD and SOD, sulfi te accumulates fi rst in mitochondria where it has been shown to increase reactive oxygen species [ 149 ]. Sulfi te also decreases ATP synthesis in mitochondria when respiring on glutamate (which is the case in the brain), while using other respiratory substrates such as malate, α-ketoglutarate, and succinate did not show any sulfi te vulnerability [ 149 ].…”
Section: Molecular Basis Of Neurodegenerationmentioning
confidence: 97%
“…Chiarani et al, [63] found that sulfite increased lipid peroxidation and decreased antioxidant enzyme defences in the rat brain. In addition, when rat and mouse neuronal cells were exposed to sulfite in vitro, there was an increase in the production of ROS and a reduction in intracellular ATP production [65]. The latter authors also found that glutamate dehydrogenase in the rat brain was inhibited by sulfites; hypothesizing that this may result in an energy deficit in the neurons, with secondary inhibition of the citric acid (TCA) cycle [65].…”
Section: Putative Mechanism Of Sulfur-induced Pemmentioning
confidence: 85%
“…Sulfite ion is a strong nucleophile and can react with wide variety of biologically important compounds to cause toxicity [63] and the neurotoxic effects of sulfite have been increasingly recognized [63,64]. One electron sulfite oxidation is thought to produce sulfite radicals that have been reported to damage DNA, lipids and proteins [65]. Chiarani et al, [63] found that sulfite increased lipid peroxidation and decreased antioxidant enzyme defences in the rat brain.…”
Section: Putative Mechanism Of Sulfur-induced Pemmentioning
confidence: 99%
See 1 more Smart Citation
“…7,11 NO production can still be achieved through a pathway involving the molybdenum dependent enzyme, xanthine oxidase. 7,13 Review of the literature reported two cases of HPS with MoCD. In-patient with MoCD and SOD, alternative NO production pathway may also be disrupted, predisposing the patient to a reduced level of NO and potentially to pyloric stenosis.…”
Section: Discussionmentioning
confidence: 99%